Type I interferon receptor blockade with anifrolumab corrects innate and adaptive immune perturbations of SLE. Issue 1 (22nd November 2018) - Casey, Kerry A; Guo, Xiang; Smith, Michael A; Wang, Shiliang; Sinibaldi, Dominic; Sanjuan, Miguel A; Wang, Liangwei; Illei, Gabor G; White, Wendy I
Abstract : Objective: Anifrolumab is a fully human immunoglobulin G1 κ monoclonal antibody specific for subunit 1 of the type I interferon (IFN) α receptor. In a phase IIb study of adults with moderate to severe SLE, anifrolumab treatment demonstrated substantial reductions in multiple clinical endpoints. Here, we evaluated serum proteins and immune cells associated with SLE pathogenesis, type I interferon gene signature (IFNGS) test status and disease activity, and how anifrolumab affected these components. Methods: Whole blood samples were collected from patients enrolled in MUSE (NCT01438489 ) for serum protein and cellular assessments at baseline and subsequent time points. Data were parsed by IFNGS test status (high/low) and disease activity. Protein expression and immune cell subsets were measured using multiplex immunoassay and flow cytometry, respectively. Blood samples from healthy donors were analysed for comparison. Results: Baseline protein expression differed between patients with SLE and healthy donors, IFNGS test-high and -low patients, and patients with moderate and severe disease. Anifrolumab treatment lowered concentrations of IFN-induced chemokines associated with B, T and other immune cell migration in addition to proteins associated with endothelial activation that were dysregulated at baseline. IFNGS test-high patients and those with high disease activity were characterised by low baseline numbers of lymphocytes, circulating memory T-cell subsets and neutrophils. Anifrolumab treatment reversed lymphopenia and neutropenia in the total population, and normalised multiple T-cell subset counts in IFNGS test-high patients compared with placebo. Conclusions: Anifrolumab treatment reversed IFN-associated changes at the protein and cellular level, indicating multiple modes of activity. Trial registration number: NCT01438489.